What is a clinically relevant change on the HIT-6 questionnaire? An estimation in a primary-care population of migraine patients. (January 2014) - Smelt, Antonia FH; Assendelft, Willem JJ; Terwee, Caroline B; Ferrari, Michel D; Blom, Jeanet W
Objective: To interpret questionnaire scores, clinicians and researchers need to know what change in score reflects a meaningful change in the condition of an individual patient, and what difference reflects a meaningful difference between groups. These values differ between different populations. We determined the within-person minimally important change (MIC) and the between-group minimally important difference (MID) of the Headache Impact Test-6 (HIT-6) questionnaire in a primary-care population of migraine patients. Methods: We included 490 patients who participated in a clinical trial on the treatment of migraine in primary care. We compared their change scores on the HIT-6 questionnaire between baseline and at three-months follow-up with the answers to two anchor questions according to the 'mean change approach' and the 'ROC curve approach'. Results: The within-person MIC was estimated to be between −2.5 points (mean change approach) and −6 points (ROC curve approach). The choice for the within-person MIC value depends on the consequences of false positives and false negatives in a particular setting. The between-group MID was estimated at −1.5 points. Conclusions: We determined the within-person MIC and between-group MID for the HIT-6 in a primary-care population of migraine patients. We recommend the use of these values for clinical care and for research.